2010
DOI: 10.1111/j.1440-1754.2010.01932.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac cirrhosis and hepatocellular carcinoma in a 13‐year‐old treated with doxorubicin microbead transarterial chemoembolization

Abstract: Increasing numbers of children are surviving into adulthood following surgery to correct or palliate congenital heart disease. This surgery can occasionally result in long-standing elevated right heart pressures and chronic hepatic venous congestion leading to cardiac cirrhosis. We report the first paediatric case of hepatocellular carcinoma in the setting of cardiac cirrhosis. A 13-year-old girl developed inoperable hepatocellular carcinoma and was treated with transarterial embolization with lipiodol and dox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 8 publications
1
30
0
Order By: Relevance
“…However, the prognosis of children and adolescents with HCC after a Fontan operation is poor. Of the 4 patients in Table 2 who were <18 years old upon diagnosis of HCC [8,10,16,17], 3 had died in the 20 years since the operation [8,10,16]. These reports suggest that surveillance for liver disease at regular intervals is essential to improve the prognosis of children with HCC after a Fontan operation.…”
Section: Liver Tumors Associated With Congenital Heart Diseasementioning
confidence: 98%
See 3 more Smart Citations
“…However, the prognosis of children and adolescents with HCC after a Fontan operation is poor. Of the 4 patients in Table 2 who were <18 years old upon diagnosis of HCC [8,10,16,17], 3 had died in the 20 years since the operation [8,10,16]. These reports suggest that surveillance for liver disease at regular intervals is essential to improve the prognosis of children with HCC after a Fontan operation.…”
Section: Liver Tumors Associated With Congenital Heart Diseasementioning
confidence: 98%
“…A PubMed interface search revealed that as of February 2019, at least 33 patients had been diagnosed with HCC after Fontan palliation (Table 2) [5][6][7][8][9][10][11][12][14][15][16][17][18][19][20][21]. Although this number is small, gender seems not to be associated with HCC.…”
Section: Liver Tumors Associated With Congenital Heart Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…3 Liver fibrosis in adults with congenital heart disease (CHD) is a growing concern, and a few cases of HCC have been reported. [4][5][6][7] Currently, only adults who have undergone a Fontan procedure are considered at risk for liver fibrosis. 8 The Fontan procedure is the last surgery in a series of palliative operations for children born with single ventricle heart defects.…”
Section: Introductionmentioning
confidence: 99%